Assessment methods for corporate responsibility on the fashion scene : a case study of Hennes & Mauritz, Lindex, Kappahl and MQ - Larsson, Anna (SLU/Dept. of Economics, 2011)
Assessing the outcome of corporate responsibility is often argued to be complicated due to long-term effects and qualitative aspects. Epstein (2008, p.261) establishes that: “Though many think that sustainability is too difficult to measure, companies have found that unless the impacts are measured, they are commonly ignored in the resource allocation process”. Corporate responsibility is often referred to as a business case, i.e., that social and environmental concern add value to the business (Heikkurinen, 2010; Porter & van der Linde, 1995). Hence, for corporate responsibility to be a business case a strategy, corporate structure and systems, programmes and actions linked to performance measures need to be in place to assess the outcome; environmental, social as well as financial. The information assessed from corporate responsibility initiatives is not exclusively of interest for the internal organisation, but is also important for stakeholder dialogue.